INSERTION OF THE FATHER IN THE CARE OF THE HOSPITALIZED PRETERM INFANT: PERCEPTION OF THE MULTIPROFESSIONAL TEAM - Natalia Cristine Soares; Maria Piassa Lourenço Bernardino; Adriana Valongo Zani
ABSTRACT Objective: To understand the perception of the multiprofessional health care team regarding the inclusion of fathers in the care of preterm infants who are in Intensive Care Units (ICUs). Methods: This is a descriptive study with a qualitative approach, using a semi-structured interview with 12 health care professionals of a neonatal ICU, from February to July 2017. The data were analyzed according to the Discourse of the Collective Subject. Results: Seven main ideas (MI) emerged from the text analysis, which were grouped into two themes: 1) the role of the father according to the multiprofessional health care team views (MI1: parent provider, MI2: shared care, MI3: supportive father); 2) perception of the father caring for the hospitalized preterm infant (MI4: father does not change diapers; MI5: father conquering new spaces; MI6: strengthening the bonding; MI7: father providing maternal security. Conclusions: The results of this study point out to the importance of including the father figure in the humanized care of preterm infants. Professional health care team should be more aware of fathers' importance in the care of hospitalized preterm infants.